Healthy Living Education for Preventing Childhood Infectious Diseases: A Literature Review - Phalis, Annisa Putri Ana; Yasin, Agustina M.; Sukmawati, Sukmawati; Sudirman, Sudirman; Yani, Ahmad; Amalinda, Finta (Pancasakti Journal Of Public Health Science And Research, 2025)
The increasing incidence of infectious diseases among children highlights the urgent necessity for effective health education programs emphasizing clean and healthy behaviors. This study aims to identify the determinants influencing the effectiveness of health education in preventing infectious diseases in children. A systematic literature review was performed, analyzing 15 peer-reviewed articles retrieved from databases including PubMed, Scopus, and Web of Science, encompassing publications from 2019 to 2024. The search strategy employed keywords such as "health education," "infectious disease prevention," and "clean and healthy behavior." Inclusion criteria comprised studies focusing on health education interventions, while exclusion criteria omitted non-peer-reviewed articles and studies irrelevant to the subject matter. The findings revealed that interactive teaching approaches substantially improved children’s comprehension and retention of health-related information. Furthermore, robust parental involvement demonstrated a positive association with the enhancement of children’s health behaviors. The review also underscored the significance of culturally sensitive educational materials and well-trained educators in delivering effective health education. In conclusion, addressing these factors is critical to optimizing the effectiveness of health education programs designed to promote clean and healthy behaviors, thereby contributing to the prevention of infectious diseases and improved health outcomes among children.